(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In the article are defined argumentation models of oratory words, having peculiar role in the history of the Kazakh people. But there are several reasons for distinguishing the Kazakh peoples’ eloquence and oratorical skill. Firstly, holders of oratory words were bi (the Kazakh orators), who having interfered in policy of leading peoples in order to harmonize relationships among individuals, between nation and nation, fulfilled the functions of a prosecutor, an advocate and an executioner. Secondly, telling to people the profoundly philosophical propaganda words and ideas about the essence of life. In the article are defined argumentation models, lying in the structure and content of the Kazakh oratory words, which are taken as the material for a rhetorical word. In the research discourse components of the oratory words, acceptance of information by a listener, the procedure of cognition process, basic concepts of the people’s national worldview are taken with due account into primary concern